2016
DOI: 10.1177/0091026016663234
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Change in Public Job Security Policy

Abstract: For most of the 20th century, public employers granted their employees high levels of job security. The 21st century has brought a reversal of fortunes, with emphasis increasingly on at-will employment systems. Both distant and recent policy choices about job security have been based largely on normative and ideological considerations rather than behavioral science evidence. This article synthesizes public-and privatesector job security research to provide a more evidence-based footing for future public job se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…They also suggested that goal clarity and job security also increase the job satisfaction to the employees. (Hur and Perry, 2016), Said that, public employees enjoyed high job security in 20 th century. In 21 st century public sector job security depends on ideological consideration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They also suggested that goal clarity and job security also increase the job satisfaction to the employees. (Hur and Perry, 2016), Said that, public employees enjoyed high job security in 20 th century. In 21 st century public sector job security depends on ideological consideration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Absence of training and development program in the organization creates employee turnover intention. This factor consists of five (5) attributes, all are highly relating with others. The most influential attribute is frequently arrangement of training program in the university.…”
Section: Training and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This was more than just good employment practice, but rather to support stability in the political environment and ensure public servants were free to provide frank and fearless advice without fear of dismissal (Pollitt & Bouckaert, 2011). Hur and Perry (2016) note that “job security is a concept of enduring importance in public administration” in the United States, and had become institutionalized and widely accepted (p. 264). However, the widespread principle of job security was often an implicit feature of employment rather than a legal entitlement, which made it susceptible to challenge amid public sector reforms in recent decades (Bach & Bordogna, 2011; Condrey & Battaglio, 2007; Hur & Perry, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hur and Perry (2016) note that “job security is a concept of enduring importance in public administration” in the United States, and had become institutionalized and widely accepted (p. 264). However, the widespread principle of job security was often an implicit feature of employment rather than a legal entitlement, which made it susceptible to challenge amid public sector reforms in recent decades (Bach & Bordogna, 2011; Condrey & Battaglio, 2007; Hur & Perry, 2016). These challenges have increased in some countries since the onset of global financial crisis (GFC; around 2008-2009 in Australia).…”
Section: Introductionmentioning
confidence: 99%